Epigenetic down‐regulation of integrin α7 increases migratory potential and confers poor prognosis in malignant pleural mesothelioma. Issue 2 (14th July 2015) - Laszlo, Viktoria; Hoda, Mir Alireza; Garay, Tamas; Pirker, Christine; Ghanim, Bahil; Klikovits, Thomas; Dong, Yawen W; Rozsas, Anita; Kenessey, Istvan; Szirtes, Ildiko; Grusch, Michael; Jakopovic, Marko; et al.
Abstract Malignant pleural mesothelioma (MPM) is a devastating malignancy characterized by invasive growth and rapid recurrence. The identification and inhibition of molecular components leading to this migratory and invasive phenotype are thus essential. Accordingly, a genome‐wide expression array analysis was performed on MPM cell lines and a set of 139 genes was identified as differentially expressed in cells with high versus low migratory activity. Reduced expression of the novel tumour suppressor integrin α7 (ITGA7) was found in highly motile cells. A significant negative correlation was observed between ITGA7 transcript levels and average displacement of cells. Forced overexpression of ITGA7 in MPM cells with low endogenous ITGA7 expression inhibited cell motility, providing direct evidence for the regulatory role of ITGA7 in MPM cell migration. MPM cells showed decreased ITGA7 expressions at both transcription and protein levels when compared to non‐malignant mesothelial cells. The majority of MPM cell cultures displayed hypermethylation of the ITGA7 promoter when compared to mesothelial cultures. A statistically significant negative correlation between ITGA7 methylation and ITGA7 expression was also observed in MPM cells. While normal human pleura samples unambiguously expressed ITGA7, a varying level of expression was found in a panel of 200 human MPM samples. In multivariate analysis, ITGA7 expression was found to be an independent prognostic factor. Although there was no correlation between histological subtypes and ITGA7 expression, importantly, patients with high tumour cell ITGA7 expression had an increased median overall survival compared to the low‐ or no‐expression groups (463 versus 278 days). In conclusion, our data suggest that ITGA7 is an epigenetically regulated tumour suppressor gene and a prognostic factor in human MPM. Copyright © 2015 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.